Formulation of Modified Dense Graded Bituminous Macadam with Low Density and High-Density Polythene Waste with Zycotherm Admixture : A Review - Kumar, Avinash; Saxena, Ajeet (International Journal of Scientific Research in Civil Engineering, 2021)
This study presents the use of waste polythene in flexible pavement construction. Reclaimed plastic waste derived as carry bags from kitchen and pond liner polyethelene as LDPE and plastic bottle caps as HDPE have been used as additive in flexible pavements. In this study we will also add a fix percentage of Zykotherm (ZycoTherm is an odor free additive that increases moisture resistance while lowering mixing and compaction temperature up to 65°F. Purposes of using above materials are to utilize environmentally unacceptable waste material and to develop a better material mix to resist increased traffic load, temperature effect and pressure resulted in cracks in the pavement surface. In the proposed study the plastic waste will be cleaned and cut into a size such that it passes through 2-3mm sieve using shredding machine. In this study we are presenting review of literatures presenting utilization of plastic in construction industry
Keywords: Bacteria; Concrete; Fibers; Strength; Self Healing; Material; Admixtures